Enfoque téorico epistemológico del comercio justo - Caso de estudio Ecuador - Cruz Villacrés, Linda Chantal (2015)
The main objective of this paper is developing a research, or an approach of the theoretical and methodological references of Fair Trade, and its situation in Ecuador. The research has considered books, laws, regulations, magazine articles and websites in order to determine the foundations and theories that defends Fair Trade. Fair trade advocates ten principles that have to do with improving the quality of human life, environmental sustainability and maintains a fair economic exchange, also is intended to support small farmers, workers, artisans and miners, through certifications that validate these parameters. In Ecuador 1% of non-oil exports has been made with Fair Trade products; however there is not deep and updated statistical data on this type of alternative trade neither in the country, nor in a defined policy to regulate any issue. The Ministry of Foreign Trade has led the development of "Ecuadorian Fair Trade Strategy", it proposes guidelines that are currently being implemented to promote, regulate and control this type of trade. Assigning a state agency that regulates the implementation of a policy that regulates Fair Trade in the country is recommended, in addition the efforts to spread its theories and support in the process.